Thermodynamics of Cadmium Sorption on Different Soils of West Bengal, India - Tanmoy Karak; Ranjit Kumar Paul; D. K. Das; Romesh K. Boruah; Indira Sonar (The Scientific World Journal)
A sorption study was conducted on different soils collected from five agroecological zones of West Bengal, India, to understand the soil environmental behavior and fate of cadmium. For this purpose batch adsorption experiments were carried out at the native soil pH and at three different temperatures (25°C, 35°C, and 45°C). The adsorption data fitted by a linear least squares technique to the different sorption isotherms. Most data obtained give the good fit to both Freundlich and modified Langmuir isotherms, but they are not consistent with the linear Langmuir adsorption model. Thermodynamic parameters, namely, thermodynamics equilibrium constant at a particular temperature T  (KT0), Gibbs free energy at a particular temperature T  (ΔGT0), and change of enthalpy (ΔH0) and change of entropy at temperature T  (ΔST0), were also determined by applying sorption value and concentrations of Cd in equilibrium solution within the temperature range. The thermodynamic parameters revealed that Cd sorption increases as the values of KT0, ΔGT0, ΔH0, and ΔST0 were increased on reaction temperatures. The spontaneous sorption reaction can be concluded due to high values of ΔGT0. The positive values of ΔH0 indicated that the Cd sorption is an endothermic one. Under these present conditions, the soil and its components possibly supply a number of sites having different adsorption energies for cadmium sorption.